Simulation Analysis and Test Verification of Automobile V-ribbed Belt Drive Noise - Yaochen Shi; Guoping Chen; Peng Zhou; Wusheng Tang (Jixie chuandong)
Taking 6PK type V-ribbed belt as the research object. Firstly， the mechanism of V-ribbed belt drive noise is analyzed， based on the method of combination of vibration characteristic analysis and acoustic boundary element analysis， the simulation and prediction model of two pulleys V-ribbed belt drive noise is established. The noise distribution nephogram and amplitude-frequency characteristic curve of V-ribbed belt drive system are obtained. Then， based on the principle of sound array technology， a noise source identification device for V-ribbed belt drive is set up， and the experimentally study of influence of rotating speed on V-ribbed belt drive noise is carried out. The frequency domain curve and noise distribution nephogram of V-ribbed belt drive noise at different rotating speeds are obtained. Finally， the comparison between simulation results and experimental results shows that in the non-resonance zone， the noise amplitude increases with the increase of rotating speed. In the resonance zone， the amplitude of the noise will increase sharply， and the amplitude of the higher order resonance is larger. The experimental results are about 4% higher than that of simulation analysis. The correctness of theoretical analysis and simulation method is verified， which provides a basis for the prediction of noise of automobile V-ribbed belt drive.